(3OQGSI bjGSjI JMdjdjI ebGQf Hjf GdLRGFQ,JhfS hGdeZQHs - (3SajGf(B, (3behejIs ((3JdeSGf(B:s (3GdecJH GdLGeYj GdMOjK(B,s, 2017)
(3eONd fXQj dJOabGJ QDhS GdCehGd GdCLfHjI(B: (3eGgjI JOabGJ QDhS GdCehGd GdGLfHjI ,GdCTcGd GdGSGSjI dJOabGJ QDhS dCehGd GdCLfHjI ,GdBKGQGdGbJUGOjI dJOabGJ QDhS GdCehGd GdGLfHjI aj Xd JMQjQ MSGH QGS GdeGd hSjGSGJ GdJMce ajgG(B. (3GdfehGdGbJUGOj hYdGbJg HJOabGJ QDhS GdGhGd GdCLfHjI ,OQGSI bjGSjI dCKQ gjcd JOabGJ QDhS GdGhGd GdCLfHjI Ydi feh GdGbJUGOj aj cd ef GdLRGFQ,JhfS hGdeZQH(B.s
(3HHdjhZQGajG(B:(3U(B.263s
Keywords: (3QCS GdeGds; (3GdJfejI GdGbJUGOjIs; (3QDhS GdGhGd GdCLfHjI s